'It reminds me that I should stop for the little moments': Exploring emotions in experiences of UK Covid-19 lockdown. (September 2022) - Bullo, Stella; Hearn, Jasmine; Webster, Lexi
In this study, we explore how participants articulate experiences of emotions during Covid-19 lockdown in the UK. We posit that emotions fulfil experiential and interpersonal functions, which are construed and conveyed through language choices. An online narrative survey was carried out. About 88 responses were analysed. Participants were from England and Wales. The mean age was 48.9 years old (SD = 62). A mixed-method approach was used. This combined quantitative Corpus Linguistics analysis and qualitative Interpretative Phenomenological Analysis with linguistic analysis. The findings show similarities to the public health and medical literature that highlight negative emotions, such as fear, distrust and anger in participants. However, we also found positive emotions not considered elsewhere, including happiness, relaxation, safety, optimism for the future and connectedness arising from the thematic IPA analysis. Emotions were construed using language explicitly labelling emotions and language implicitly signalling emotions. Our study highlights implications for managing risk behaviours associated with transmission in public health practices such as social distancing, as indicated by negative emotions. We also bring to light implications with perceived benefits of engaging in protective behaviours and social support central to public health measures, as suggested by the communication of positive emotions.